PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWERPOINT INTERAKTIF MELALUI PENDEKATAN SAINTIFIK PADA SISWA SD - Azzahra, Yesi (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
The 21st century is the era of globalization characterized by mutual openness and interdependence between countries. As a result of mutual openness and dependence coupled with a very fast flow of information, competence between countries will be even tighter. Global life is both a challenge and an opportunity to gain opportunities for economic development. This is when it is necessary to increase the quality of education in order to create quality human resources. In the 21st century, the human resources needed are those who have the ability to communicate, collaborate, be creative, and think critically. Through the development of SD learning media it is hoped that it can increase student learning motivation so that the results achieved can be maximized. The purpose of preparing this design is to create educational innovation, especially in the learning process through the development of interactive PowerPoint-based learning media through a scientific approach to elementary students. The approach used is Research and Development. With the preparation of educational innovation designs it is expected to be able to improve the quality of education, especially in elementary schools.